Synthesis and characterization of reversible and self‐healable networks based on acylhydrazone groups. Issue 9 (7th March 2014) - Apostolides, Demetris E; Patrickios, Costas S; Leontidis, Epameinondas; Kushnir, Michelle; Wesdemiotis, Chrys
<x xml:space="preserve">Abstract</x> Dynamic covalent networks based on pentaerythritol tetra(benzohydrazide) and 1, 10‐decanediol dibenzaldehyde were prepared, and their swelling and self‐healing properties were investigated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>